The anatomy of the carotico-clinoid foramen and its relation with the internal carotid artery - ÖZDOĞMUŞ, NECMETTİN ÖMER (SPRINGER FRANCE, 2003)
The carotico-clinoid foramen is the result of ossification either of the carotico-clinoid ligament or of a dural fold extending between the anterior and middle clinoid processes of the sphenoid bone. It is anatomically important due to its relations with the cavernous sinus and its content, sphenoid sinus and pituitary gland. In this study the ossification state of the carotico-clinoid ligament, the diameter of the internal carotid artery and the carotico-clinoid foramen has been studied on 50 autopsy cases. Of the 100 carotico-clinoid foramina examined, in 27 sides (15 right, 12 left) the carotico-clinoid ligament was completely ossified, in 18 sides (9 right, 9 left) the carotico-clinoid ligament was incompletely ossified and in 55 sides (26 right, 29 left) it was a ligamentous structure. The correlation of the dimensions of the carotico-clinoid foramen and the internal carotid artery showed no statistical significance, except between the carotico-clinoid foramen with a fibrous carotico-clinoid ligament and the internal carotid artery on the right side (p=0.007, r=0.51). The existence of a bony carotico-clinoid foramen may cause compression, tightening or stretching of the internal carotid artery. Further, removing the anterior clinoid process is an important step in regional surgery; the presence of a bony carotico-clinoid foramen may have high risk. Therefore, detailed knowledge of the type of ossification between the anterior and middle clinoid processes can be necessary to increase the success of regional surgery.
Keywords: carotico-clinoid foramen; internal carotid artery; anterior clinoid process; middle clinoid process; anterior clinoidectomy; CAVERNOUS SINUS; OPHTHALMIC ANEURYSMS; REGION